Model Intervensi Berbasis Komunitas untuk Pencegahan Obesitas pada Remaja di Era Gaya Hidup Digital - Isnaini Isnaini; Sajaroni Sajaroni; Syahrial Adam (Journal of Medical and Health Science, 2026)
The increasing prevalence of obesity in adolescents is a major public health challenge in the digital lifestyle era. Changes in activity patterns, increased use of digital devices, and high-energy food consumption habits contribute to the increased risk of obesity in adolescents. This study aims to develop and analyze the effectiveness of a community-based intervention model to prevent obesity in adolescents living in a digital environment. The study used a quantitative approach with a quasi-experimental design involving adolescents aged 13–18 years as respondents. The intervention was implemented through a nutrition education program, community-based physical activity enhancement, and the use of a digital platform for monitoring health behaviors. Data were collected through health behavior surveys, body mass index measurements, and physical activity observations before and after the intervention. The results showed that the community-based intervention model was able to improve adolescents' nutritional knowledge, encourage changes in food consumption patterns, and increase participation in physical activity. The use of digital technology in the intervention program was also shown to increase participant engagement and facilitate the process of monitoring health behaviors. In addition, social support from family, school, and community plays a crucial role in maintaining healthy behavior changes in adolescents. This study concludes that integrating a community approach and digital technology can be an effective strategy in preventing obesity in adolescents. The intervention model developed has the potential to be applied more widely in community-based health promotion programs in the digital era.